The Relation of Financial, Tax and Administrative Responsibility - Barashyan, Liana R. (International Review of Management and Marketing, 2016)
The tax system and the corresponding area of legal regulation of a new type is emerging in Russia for almost 15 years, but the problems of efficiency of the tax liability lately has been paying more and more attention. Tax ratio has a complex economic-legal nature. The economic content of tax relations is mediated by macroeconomic parameters of national economic policy, statistical parameters of tax planning and tax administration. The beginning of the tax administrative relationships manifest in the power relations on establishment, introduction, collection of taxes and fees, as well as fiscal control. The constitutional principle of separation of powers determines the administrative and judicial procedure for appealing against acts of tax authorities and actions and inactions of their officials. This article is devoted to analysis of the problems associated with the content, structure of tax legal relations, similar to this aspect of the problem of tax offences, their classification and establishing the appropriate tax liability for committing them. The article examines the nature and types of taxation, the tax legal relations, rights and duties of subjects of tax relations. Keywords: administrative responsibility, tax responsibility, financial responsibility, regulation, policy JEL Classifications: H20, F62, G38